2022
DOI: 10.1101/2022.03.31.485989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Affecting Protein Recovery During Hsp40 Affinity Profiling

Abstract: Hsp40s play a central role in cellular protein homeostasis by promiscuously surveying the proteome for misfolded proteins. These misfolded client proteins are then delivered to Hsp70. Mutation of the Hsp40 J-domain blocks Hsp70 binding, inhibiting client protein release from Hsp40. We previously integrated misfolded protein recognition by Hsp40 into a platform to identify proteins that are destabilized by cellular stress. However, the dependences of Hsp40 interactions and client recovery on J-domain activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…170 Even brief, mild heat shock induces monotonic increased association, consistent with DNAJB8 H31Q affinity reflecting protein destabilization. 171…”
Section: Methods For Characterizing Protein Damagementioning
confidence: 99%
See 2 more Smart Citations
“…170 Even brief, mild heat shock induces monotonic increased association, consistent with DNAJB8 H31Q affinity reflecting protein destabilization. 171…”
Section: Methods For Characterizing Protein Damagementioning
confidence: 99%
“…After surveying various J-domain proteins, we found that the human J-domain protein mutant, DNAJB8 H31Q , strongly binds destabilized proteins allowing their affinity purification. 170,171 This binding is resistant to strong detergent buffer, allowing stringent purification conditions prior to quantitative proteomics. The DNAJB8 H31Q associated proteome is destabilized compared to the bulk proteome.…”
Section: Protein Stability Through Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously developed an affinity purification mass spectrometry (AP-MS) approach to profile the misfolded proteome based on its affinity to the human Hsp40 DNAJB8 (Figure B) . This assay combines affinity purification of overexpressed Flag DNAJB8 H31Q with quantitative proteomics to identify hundreds of coisolating cellular proteins with high reproducibility and statistical confidence. , The H31Q mutation blocks the release of misfolded proteins from DNAJB8, making it a thermodynamic sink for its clients. This binding is highly detergent-resistant, allowing immunoprecipitates to be stringently washed.…”
Section: Introductionmentioning
confidence: 99%
“…We previously developed an affinity purification mass spectrometry (AP-MS) approach to profile the misfolded proteome using human the Hsp40 DNAJB8 37 . This assay combines affinity purification of overexpressed Flag DNAJB8 H31Q with quantitative proteomics to identify hundreds of co-isolating cellular proteins with high reproducibility and statistical confidence 38,39 . The H31Q mutation blocks the release of misfolded protein clients from DNAJB8, making it a thermodynamic sink for its clients.…”
Section: Introductionmentioning
confidence: 99%